Tweede van links: Planken; rechts daarnaast Van Dam, ?, Van Mierlo. Zittend met bril in hand, Den Uyl - Toussaint, Dolf, (1972)
Tweede van links: Planken; rechts daarnaast Van Dam, ?, Van Mierlo. Zittend met bril in hand, Den Uyl.